Pregnant women's experiences with the management of hypertensive disorders of pregnancy: a qualitative study - Amyna Helou; Kay Stewart; Kath Ryan; Johnson George (BMC, 2021)
Abstract Background Hypertensive disorders are a leading cause of mortality and morbidity during pregnancy. Despite multiple national and international clinical guidelines and a plethora of research in the field of optimising management, there has been limited research describing the perspectives and experiences of pregnant women with the management of hypertensive disorders of pregnancy (HDP). Understanding these perceptions and experiences is imperative to the optimisation of HDP management. Methods A qualitative study involving face-to-face, in-depth interviews were undertaken with 27 pregnant women diagnosed with and being treated for HDP to explore their perspectives of and experiences with clinical management. Written consent was obtained individually from each participant, and the interviews ranged from 16 to 54 min. Inductive codes were generated systematically for the entire data set. Line-by-line analysis was then performed and nodes were created within NVivo, a qualitative data management software. Data collection was continued until thematic saturation was reached. Thematic analysis was employed to interpret the data. Results Three major descriptive themes were discerned regarding the women's perspectives on and experiences with the management of HDP: attitudes towards monitoring of HDP, attitudes and perceptions towards development and management of complications, and perceptions of pregnant women with chronic hypertension. Trust in the hospital system, positive attitudes towards close blood pressure monitoring as well as self-monitoring of blood pressure, and a realistic approach to emergency antenatal hospital admissions contributed to a positive attitude towards monitoring of HDP. Women with prior experiences of HDP complications, including pre-eclampsia, were more confident in their clinical management and knew what to expect. Those without prior experience were often in shock when they developed pre-eclampsia. Some women with chronic hypertension displayed limited understanding of the potential risks that they may experience during pregnancy and thus lacked comprehension of the seriousness of the condition. Conclusions The clinical management experiences of pregnant women with HDP were varied. Many women did not feel that they were well informed of management decisions and had a desire to be more informed and involved in decision-making. Clear, concise information about various facets of HDP management including blood pressure monitoring, prescription of the appropriate antihypertensive agent, and planning for potential early delivery are required.